Clinical course and characterisation of lymphangioleiomyomatosis in a Brazilian reference centre - Baldi, Bruno Guedes; Freitas, Carolina Salim Gonçalves; Araujo, Mariana Sponholz; Dias, Olívia Meira; Pereira, Daniel Antunes Silva; Pimenta, Suzana Pinheiro; Kairalla, Ronaldo Adib; Carvalho, Carlos Roberto Ribeiro (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2014)
Background and objective: Lymphangioleiomyomatosis (LAM) is a rare disease that promotes pulmonary cystic destruction and impairs pulmonary function. We aim to describe features and clinical course of LAM patients from Brazil. Methods: We described the clinical and functional features, performance in six minute walk test (6MWT), management details, survival and clinical course of 84 LAM patients followed in a Brazilian reference centre. Results: All subjects were women, the average age at onset of symptoms was 38 years, and the average at diagnosis was 42 years. The major symptoms during the course of the disease were dyspnoea and pneumothorax. The patients experienced impaired quality of life, with worse scores in the physical and emotional domains. The most common abnormalities in pulmonary function tests were an obstructive pattern and reduced diffusion capacity, whereas a quarter of the patients had normal spirometric results. In the 6MWT, although patients had preserved exercise capacity, more than half of the patients had significant desaturation. Hormonal blockage and doxycycline were the most common treatment modalities employed in our patients. The survival probability from diagnosis was 90% at 5 years, whereas the mean annual rate of decline in FEV1 was 60 ± 78 mL. Conclusions: Clinical and functional features of the LAM patients from our centre are similar to those from other countries. Our sample showed preserved exercise capacity, with desaturation in the 6MWT, and impaired quality of life. Survival was similar, whereas the annual rate of decline of FEV1 was slightly lower than in recent studies.